Finite element (quasi-static) model of electrostatic microelectromechanical cantilever - Lai, Adriana Mook Kim (Universiti Malaysia Sarawak, UNIMAS, 2009)
A finite element model has been developed to enable an initial assessment of the analysis of an elastic-electrostatic system of an electrostatic micromechanical cantilever (which is often referred to simply as a cantilever) for microelectromechanical systems (MEMS) design performance and evaluation. The model comprised of an electrostatic and a mechanical solver. The electrostatic solver derived the electrostatic force on the cantilever from the potential difference applied between the cantilever and a fixed reference plate. The force is then fed to the mechanical solver that computed the deformation of the cantilever. Solutions to the solvers were attained interatively. It was assumed that the system was in quasi-static equilibrium for each interative step, as the time taken for redistribution of electric charges on the surface of the cantilever was much shorter in comparison of the mechanical reaction time of the cantilever.